Reprogramming Tumour-Associated Macrophages in Hepatocellular Carcinoma: From Molecular Mechanisms to Immunotherapeutic Strategies - Song, Xinyu (International Journal of Public Health and Medical Research, 2026)
Hepatocellular carcinoma (HCC) is still one of the top causes of cancer-related mortalities worldwide, and immunosuppressive tumour microenvironment (TME) is a key obstacle for effective therapy. Tumour-associated macrophages (TAMs) are one of the most abundant immune cells in the HCC TME and display a pro-tumourigenic character, which is related with immunosuppression, angiogenesis and resistance to systemic therapy. Reprogramming TAMs from M2-like pro-tumourigenic to an anti-tumour M1-like state has appeared as a viable therapeutic strategy. Herein we discuss the molecular pathways involved in TAM polarisation in HCC, including the CSF1R, PI3Kγ and NF-κB/STAT3 signalling pathways and review the therapeutic approaches targeting TAM re-programming including CSF1R inhibition, TLR agonists, combination with immune checkpoint blockade, CAR-macrophage engineering and nanoparticle-mediated delivery. We also highlight the clinical challenges of TAM-targeted therapy such as phenotypic plasticity and off-target toxicity, and markers for patient stratification.